2016
DOI: 10.1111/poms.12427
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Hubs for the Global Vehicle Supply Chain in Humanitarian Operations

Abstract: W e model the global vehicle supply chain of an International Humanitarian Organization (IHO) with a dynamic hub location model across monthly periods. We use actual vehicle data from the International Federation of the Red Cross to feed our model and provide insights into IHO secondary support demand. We find that secondary support demand for items such as vehicles is different from primary beneficiary demand for items such as water and food. When considering disaster response and development program demand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 27 publications
4
78
0
1
Order By: Relevance
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
See 2 more Smart Citations
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Other approaches include that of Kunz et al (2015), who concluded that UNHCR can save costs by centralising its fleet management programme; and that of Jahre and Heigh (2008), who found that a combination of postponement and strategic stocks significantly improves the speed, cost and quality of IFRC's response. Further, Aaki and Pedraza Martinez (2016) and Besiou et al (2014) showed that non-earmarked donations (postponement) improve operational performance; while Stauffer et al (2015) showed how temporary hubs (postponement) for their global fleet gives IFRC an opportunity to use of earmarked funding in a good way. These examples illustrate how combining different SCS may reduce certain risks without increasing others.…”
Section: Type Of Risk Reference Abnormalmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception is Nooraie and Parast (2016), who modeled the trade-off between increased investment in supply chain capabilities and reduced supply chain risks. Other examples are the studies of fleet management by Pedraza-Martinez et al (2011), Besiou et al (2014), andStauffer et al (2015). Further research could build on their approaches.…”
Section: A Proposed Research Agendamentioning
confidence: 99%
“…The use of existing resources in the commercial sector has been suggested; for example, 'en route' vessels functioning as sea-based warehouses (Wilberg and Olafsen, 2012). Jahre et al (2016) studied the effect of integrating supply chains for emergencies with those for long-term operations through joint stock prepositioning, while Stauffer et al (2015) and Besiou et al (2015) looked specifically at fleet management. An interesting avenue for future research would be to systematically compare these and other alternatives in various types of situations; for example, using the factors suggested by Kunz and Reiner (2012).…”
Section: A Proposed Research Agendamentioning
confidence: 99%